Membuka Akses Generasi Zenial Dengan Meningkatkan Literasi dan Keterampilan Investasi Melalui Pembentukan Galeri Edukasi - Kurniawan, Dian; Fahmi, Annas Syams Rizal; Budiman, Asep; Mulyani, Elis Listiana; Paturochman, Iwan Ridwan; Kurniawati, Ane; Rinandiyana, Lucky Radi; Badriatin, Tine (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Generation Z has great potential to change the economy, but low literacy and investment skills can hinder their ability to achieve financial independence and manage their finances effectively. Therefore, the aim of this service is to provide literacy related to finance and investment to help them manage their finances wisely, fundamentally change their views on finances, and enable them to make smarter investment decisions and build a more stable and financial future. sustainable. The methods used in this service include the establishment of an Education Gallery which is designed to provide information, training and resources related to financial literacy and investment. This gallery will hold various activities such as seminars, Focus Group Discussions, as well as provide educational material that is easily accessible and understood by generation Z. The targeted output of this service is increasing the level of literacy and investment skills among generation Z. With the hope that after participating in this program, generation Z will be able to understand the concept of financial management, the basic concepts of investment, understand the risks and opportunities in investing, and be able to make better financial plans for their future. Thus, through innovative and sustainable approaches such as the establishment of the Education Gallery, this community service aims to make a significant contribution in improving the welfare and financial sustainability of generation Z, as well as strengthening the economic foundation of society as a whole, This can be seen from the results of the post-test of participants after taking part in the training, their understanding of investment has increased.